Atient Complaints Towards the Field of Surgery in Türkiye: An Analysis of Comments on the Digital Platform - Adem Şentürk; Mevlüt Yordanagil (Sakarya Tıp Dergisi)
Purpose: The purpose of the research is to examine patient complaints made on the “sikayetvar. com” website regarding the field of General Surgery in medicine in Türkiye Method: In this retrospective study, complaints made to the “sikayetvar.com” website were examined using the content analysis method, one of the qualitative research methods. In the research, 359 posts on the internet about the General Surgery specialty in medicine in Türkiye, made on the “sikayetvar.com” website between January 1, 2023 and November 1, 2023, were examined. Complaints made; They are classified according to gender, whether the institution belongs to a public or private hospital, whether it is an inpatient, outpatient or emergency patient, type of surgical intervention, number of views of the complaint and the subject of the complaint.Results: In the research, 335 (93.3%) of the complaints are related to interventions in the field of General Surgery. It was observed that 74 (20.6%) of the complaints were responded to. It was observed that the complaints from all outpatient clinic patients were significantly higher than the complaints from the service, patients who underwent surgical intervention, and patients who underwent endoscopy (p<0.05). Of the complaint categories, 214 (12.6%) were about lack of communication, 173 (10.2%) were about staff attitude, 159 (9.4%) were about lack of compassion, and 145 (8.5%) were about access and acceptance. It has been found to be related to vision.Conclusion: Knowing the sources of patient dissatisfaction in general surgery department services may help to reduce the number of patient complaints and improve patient care. It is thought that these results may guide healthcare managers on effective complaint management and help to increase patient satisfaction.